2002
DOI: 10.1207/s15327914nc421_11
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Vitamin A Intake Alters Susceptibility to Mammary Carcinogenesis in the Sprague-Dawley Rat

Abstract: We tested the hypothesis that adolescent dietary vitamin A intake impacts mammary gland development and subsequent sensitivity to carcinogenesis. Sprague-Dawley rats were fed a purified diet that was vitamin A deficient, adequate (2.2 mg retinyl palmitate/kg diet), or supranutritional (16 mg retinyl palmitate/kg diet) from 21 to 63 days of age, the period of adolescent mammary gland development. At 73 days of age, rats were given 1-methyl-1-nitrosourea (25 mg/kg body wt i.p.) and monitored for mammary tumors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Other dietary compounds, when exposed during lactation that have been reported to reduce susceptibility to malignant transformation in the mammary gland include low fat n-3 polyunsaturated fatty acids (n-3 PUFA) [12], conjugated linoleic acid (CLA) [13], flaxseed [46], and resveratrol [15]. Deficient or excessive amount of Vitamin A [47] or high fat n-3 PUFA [12] in the prepubertal diet increases mammary tumorigenesis, and an exposure to epigallocatechin-3-gallate (EGCG), the major catechin found in green tea does not modify later chemically induced mammary cancer risk [15]. Studies investigating the effects of CLA [13], vitamin A [47], resveratrol and EGCG [15] on mammary tumorigenesis exposed rats to these compounds either from weaning until the carcinogen exposure or from birth throughout the rest of the study.…”
Section: Exposures During Postnatal Period and Breast Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Other dietary compounds, when exposed during lactation that have been reported to reduce susceptibility to malignant transformation in the mammary gland include low fat n-3 polyunsaturated fatty acids (n-3 PUFA) [12], conjugated linoleic acid (CLA) [13], flaxseed [46], and resveratrol [15]. Deficient or excessive amount of Vitamin A [47] or high fat n-3 PUFA [12] in the prepubertal diet increases mammary tumorigenesis, and an exposure to epigallocatechin-3-gallate (EGCG), the major catechin found in green tea does not modify later chemically induced mammary cancer risk [15]. Studies investigating the effects of CLA [13], vitamin A [47], resveratrol and EGCG [15] on mammary tumorigenesis exposed rats to these compounds either from weaning until the carcinogen exposure or from birth throughout the rest of the study.…”
Section: Exposures During Postnatal Period and Breast Cancer Riskmentioning
confidence: 99%
“…Deficient or excessive amount of Vitamin A [47] or high fat n-3 PUFA [12] in the prepubertal diet increases mammary tumorigenesis, and an exposure to epigallocatechin-3-gallate (EGCG), the major catechin found in green tea does not modify later chemically induced mammary cancer risk [15]. Studies investigating the effects of CLA [13], vitamin A [47], resveratrol and EGCG [15] on mammary tumorigenesis exposed rats to these compounds either from weaning until the carcinogen exposure or from birth throughout the rest of the study. In the other studies, dietary exposures took place before weaning between postnatal postnatal weeks 1 and 3.…”
Section: Exposures During Postnatal Period and Breast Cancer Riskmentioning
confidence: 99%
“…For example, during development excess vitamin A leads to i) inhibition of keratinization and metaplastic transformation of the epidermis into a mucus-secreting epithelium [8], ii) enhancement of duct cell formation and down regulation of milk protein expression in the mammary glands [9], and iii) alteration of gene expression in tracheobronchial epithelium [10]. In the stomach, while it has been reported that vitamin A plays a cytoprotective role against gastric ulcer [11], Chiba and Arima [12] found that incubation of isolated gastric mucosal cells of newborn rats or young humans with vitamin A for 48 h stimulates acid secretion.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, vitamin A-deficient and -supplemented rats develop more carcinogen-induced mammary tumors than animals fed vitamin A-adequate diets (Metz et al 2002).…”
Section: Dietary Intake Of Vitamin a And Breast Cancermentioning
confidence: 97%